GE_GERICHTE P/10131/2022 vom 7. Mai 2024 - GE Cour de justice (2024)
DÉTOURNEMENT DE RETENUES SUR LES SALAIRES;RÉVISION(DÉCISION);SAISIE DE SALAIRE;GESTION DÉLOYALE | cp.159; cp.324.al5; cp.158.al1; cpp.410.al1.leta; cpp.410.al1.letb